The fifth mountain - Coelho, Paulo; Landers, Clifford E (New York HarperFlamingo, 1998)
"In this retelling and extensive extrapolation of the story of the Hebrew prophet Elijah, Coelho situates his New Age prose in an appropriate biblical setting. An excellent and faithful translation willing to follow the rhythms and belabored biblical style of the original"--Handbook of Latin American Studies, v. 58
1 13
Keywords: Elijah -- (Biblical prophet) -- Fiction; Bible -- Fiction; Bible stories; Religious fiction